Chimeric Antigen Receptor Based Therapy as a Potential Approach in Autoimmune Diseases: How Close Are We to the Treatment? - Sadeqi Nezhad, Muhammad; Seifalian, Alexander; Bagheri, Nader; Yaghoubi, Sajad; Karimi, Mohammad Hossein; Adbollahpour-Alitappeh, Meghdad (Frontiers in Immunology, 2020)
Despite significant breakthroughs in the understanding of immunological and physiological features of autoimmune diseases, currently, there is no specific therapeutic option with prolonged remission. Cell-based therapy using engineered T cells has attracted tremendous attention as a practical treatment for autoimmune diseases. Genetically modified-T cells armed with chimeric antigen receptors (CARs) attack autoreactive immune cells such as B cells or antibody-secreting plasma cells. CARs can further guide the effector and regulatory T cells (Tregs) to the autoimmune milieu to traffic, proliferate, and exert suppressive functions. The genetically modified-T cells with artificial receptors are a promising option to suppress autoimmune manifestation and autoinflammatory events. Interestingly, CAR-T cells are modified to a new chimeric auto-antibody receptor T (CAAR-T) cell. This cell, with its specific-antigen, recognizes and binds to the target autoantibodies expressing autoreactive cells and, subsequently, destroy them. Preclinical studies of CAR-T cells demonstrated satisfactory outcomes against autoimmune diseases. However, the lack of target autoantigens remains one of the pivotal problems in the field of CAR-T cells. CAR-based therapy has to pass several hurdles, including stability, durability, trafficking, safety, effectiveness, manufacturing, and persistence, to enter clinical use. The primary goal of this review was to shed light on CAR-T immunotherapy, CAAR-T cell therapy, and CAR-Treg cell therapy in patients with immune system diseases.